The virtual community homesteading on the electronic frontier - Rheingold, Howard 1947- (Addison-Wesley, 1993)
The technology news is filled with money as corporate moguls from Hollywood, the cable business, the computer industry, and the telephone companies scramble to exploit America's much ballyhooed "Electronic Superhighway". Suddenly, the interlinked network for computerized communication that grew up quietly on its own is gushing "Infotainment" possibilities. Interactive is the buzz word today, alongside convergence, cyberspace, and digital future. In The Virtual Community, Howard Rheingold returns the focus of our attention to people, working back from this commercialized present to the very beginnings of computer-mediated communication, giving us the lay of the land before it was discovered by government and the corporate giants
Keywords: Bulletinboards; Computernetwerken; Internet - Aspect social; Internet; Politieke aspecten; Réseaux d'ordinateurs - Aspect social; Sociale aspecten; Gesellschaft; Politik; Computer networks -- Social aspects; Internet -- Social aspects; Zwischenmenschliche Beziehung; Virtuelle Realität; Informationsgesellschaft; Zukunft; Cyberspace